forked from agda/agda-stdlib
-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathProperties.agda
310 lines (244 loc) · 14.7 KB
/
Properties.agda
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
------------------------------------------------------------------------
-- The Agda standard library
--
-- Propertiers of any for containers
------------------------------------------------------------------------
{-# OPTIONS --cubical-compatible --safe #-}
module Data.Container.Relation.Unary.Any.Properties where
open import Level
open import Algebra
open import Data.Product as Prod using (∃; _×_; ∃₂; _,_; proj₂)
open import Data.Product.Function.NonDependent.Propositional using (_×-cong_)
import Data.Product.Function.Dependent.Propositional as Σ
open import Data.Sum.Base using (_⊎_; inj₁; inj₂; [_,_])
open import Function.Base
open import Function.Equality using (_⟨$⟩_)
open import Function.Equivalence using (equivalence)
open import Function.HalfAdjointEquivalence using (_≃_; ↔→≃)
open import Function.Inverse as Inv using (_↔_; inverse; module Inverse)
open import Function.Related as Related using (Related; SK-sym)
open import Function.Related.TypeIsomorphisms
open import Relation.Unary using (Pred ; _∪_ ; _∩_)
open import Relation.Binary.Core using (REL)
open import Relation.Binary.PropositionalEquality as P
using (_≡_; _≗_; refl)
open Related.EquationalReasoning hiding (_≡⟨_⟩_)
private
module ×⊎ {k ℓ} = CommutativeSemiring (×-⊎-commutativeSemiring k ℓ)
open import Data.Container.Core
import Data.Container.Combinator as C
open import Data.Container.Combinator.Properties
open import Data.Container.Related
open import Data.Container.Relation.Unary.Any as Any using (◇; any)
open import Data.Container.Membership
module _ {s p} (C : Container s p) {x} {X : Set x} {ℓ} {P : Pred X ℓ} where
-- ◇ can be unwrapped to reveal the Σ type
↔Σ : ∀ {xs : ⟦ C ⟧ X} → ◇ C P xs ↔ ∃ λ p → P (proj₂ xs p)
↔Σ {xs} = inverse ◇.proof any (λ _ → P.refl) (λ _ → P.refl)
-- ◇ can be expressed using _∈_.
↔∈ : ∀ {xs : ⟦ C ⟧ X} → ◇ C P xs ↔ (∃ λ x → x ∈ xs × P x)
↔∈ {xs} = inverse to from (λ _ → P.refl) (to∘from) where
to : ◇ C P xs → ∃ λ x → x ∈ xs × P x
to (any (p , Px)) = (proj₂ xs p , (any (p , P.refl)) , Px)
from : (∃ λ x → x ∈ xs × P x) → ◇ C P xs
from (.(proj₂ xs p) , (any (p , refl)) , Px) = any (p , Px)
to∘from : to ∘ from ≗ id
to∘from (.(proj₂ xs p) , any (p , refl) , Px) = P.refl
module _ {s p} {C : Container s p} {x} {X : Set x}
{ℓ₁ ℓ₂} {P₁ : Pred X ℓ₁} {P₂ : Pred X ℓ₂} where
-- ◇ is a congruence for bag and set equality and related preorders.
cong : ∀ {k} {xs₁ xs₂ : ⟦ C ⟧ X} →
(∀ x → Related k (P₁ x) (P₂ x)) → xs₁ ∼[ k ] xs₂ →
Related k (◇ C P₁ xs₁) (◇ C P₂ xs₂)
cong {k} {xs₁} {xs₂} P₁↔P₂ xs₁≈xs₂ =
◇ C P₁ xs₁ ↔⟨ ↔∈ C ⟩
(∃ λ x → x ∈ xs₁ × P₁ x) ∼⟨ Σ.cong Inv.id (xs₁≈xs₂ ×-cong P₁↔P₂ _) ⟩
(∃ λ x → x ∈ xs₂ × P₂ x) ↔⟨ SK-sym (↔∈ C) ⟩
◇ C P₂ xs₂ ∎
-- Nested occurrences of ◇ can sometimes be swapped.
module _ {s₁ s₂ p₁ p₂} {C₁ : Container s₁ p₁} {C₂ : Container s₂ p₂}
{x y} {X : Set x} {Y : Set y} {r} {P : REL X Y r} where
swap : {xs : ⟦ C₁ ⟧ X} {ys : ⟦ C₂ ⟧ Y} →
let ◈ : ∀ {s p} {C : Container s p} {x} {X : Set x} {ℓ} → ⟦ C ⟧ X → Pred X ℓ → Set (p ⊔ ℓ)
◈ = λ {_} {_} → flip (◇ _) in
◈ xs (◈ ys ∘ P) ↔ ◈ ys (◈ xs ∘ flip P)
swap {xs} {ys} =
◇ _ (λ x → ◇ _ (P x) ys) xs ↔⟨ ↔∈ C₁ ⟩
(∃ λ x → x ∈ xs × ◇ _ (P x) ys) ↔⟨ Σ.cong Inv.id $ Σ.cong Inv.id $ ↔∈ C₂ ⟩
(∃ λ x → x ∈ xs × ∃ λ y → y ∈ ys × P x y) ↔⟨ Σ.cong Inv.id (λ {x} → ∃∃↔∃∃ (λ _ y → y ∈ ys × P x y)) ⟩
(∃₂ λ x y → x ∈ xs × y ∈ ys × P x y) ↔⟨ ∃∃↔∃∃ (λ x y → x ∈ xs × y ∈ ys × P x y) ⟩
(∃₂ λ y x → x ∈ xs × y ∈ ys × P x y) ↔⟨ Σ.cong Inv.id (λ {y} → Σ.cong Inv.id (λ {x} →
(x ∈ xs × y ∈ ys × P x y) ↔⟨ SK-sym Σ-assoc ⟩
((x ∈ xs × y ∈ ys) × P x y) ↔⟨ Σ.cong (×-comm _ _) Inv.id ⟩
((y ∈ ys × x ∈ xs) × P x y) ↔⟨ Σ-assoc ⟩
(y ∈ ys × x ∈ xs × P x y) ∎)) ⟩
(∃₂ λ y x → y ∈ ys × x ∈ xs × P x y) ↔⟨ Σ.cong Inv.id (λ {y} → ∃∃↔∃∃ {B = y ∈ ys} (λ x _ → x ∈ xs × P x y)) ⟩
(∃ λ y → y ∈ ys × ∃ λ x → x ∈ xs × P x y) ↔⟨ Σ.cong Inv.id (Σ.cong Inv.id (SK-sym (↔∈ C₁))) ⟩
(∃ λ y → y ∈ ys × ◇ _ (flip P y) xs) ↔⟨ SK-sym (↔∈ C₂) ⟩
◇ _ (λ y → ◇ _ (flip P y) xs) ys ∎
-- Nested occurrences of ◇ can sometimes be flattened.
module _ {s₁ s₂ p₁ p₂} {C₁ : Container s₁ p₁} {C₂ : Container s₂ p₂}
{x} {X : Set x} {ℓ} (P : Pred X ℓ) where
flatten : ∀ (xss : ⟦ C₁ ⟧ (⟦ C₂ ⟧ X)) →
◇ C₁ (◇ C₂ P) xss ↔
◇ (C₁ C.∘ C₂) P (Inverse.from (Composition.correct C₁ C₂) ⟨$⟩ xss)
flatten xss = inverse t f (λ _ → P.refl) (λ _ → P.refl) where
◇₁ = ◇ C₁; ◇₂ = ◇ C₂; ◇₁₂ = ◇ (C₁ C.∘ C₂)
open Inverse
t : ◇₁ (◇₂ P) xss → ◇₁₂ P (from (Composition.correct C₁ C₂) ⟨$⟩ xss)
t (any (p₁ , (any (p₂ , p)))) = any (any (p₁ , p₂) , p)
f : ◇₁₂ P (from (Composition.correct C₁ C₂) ⟨$⟩ xss) → ◇₁ (◇₂ P) xss
f (any (any (p₁ , p₂) , p)) = any (p₁ , any (p₂ , p))
-- Sums commute with ◇ (for a fixed instance of a given container).
module _ {s p} {C : Container s p} {x} {X : Set x}
{ℓ ℓ′} {P : Pred X ℓ} {Q : Pred X ℓ′} where
◇⊎↔⊎◇ : ∀ {xs : ⟦ C ⟧ X} → ◇ C (P ∪ Q) xs ↔ (◇ C P xs ⊎ ◇ C Q xs)
◇⊎↔⊎◇ {xs} = inverse to from from∘to to∘from
where
to : ◇ C (λ x → P x ⊎ Q x) xs → ◇ C P xs ⊎ ◇ C Q xs
to (any (pos , inj₁ p)) = inj₁ (any (pos , p))
to (any (pos , inj₂ q)) = inj₂ (any (pos , q))
from : ◇ C P xs ⊎ ◇ C Q xs → ◇ C (λ x → P x ⊎ Q x) xs
from = [ Any.map₂ inj₁ , Any.map₂ inj₂ ]
from∘to : from ∘ to ≗ id
from∘to (any (pos , inj₁ p)) = P.refl
from∘to (any (pos , inj₂ q)) = P.refl
to∘from : to ∘ from ≗ id
to∘from = [ (λ _ → P.refl) , (λ _ → P.refl) ]
-- Products "commute" with ◇.
module _ {s₁ s₂ p₁ p₂} {C₁ : Container s₁ p₁} {C₂ : Container s₂ p₂}
{x y} {X : Set x} {Y : Set y} {ℓ ℓ′} {P : Pred X ℓ} {Q : Pred Y ℓ′} where
×◇↔◇◇× : ∀ {xs : ⟦ C₁ ⟧ X} {ys : ⟦ C₂ ⟧ Y} →
◇ C₁ (λ x → ◇ C₂ (λ y → P x × Q y) ys) xs ↔ (◇ C₁ P xs × ◇ C₂ Q ys)
×◇↔◇◇× {xs} {ys} = inverse to from (λ _ → P.refl) (λ _ → P.refl)
where
◇₁ = ◇ C₁; ◇₂ = ◇ C₂
to : ◇₁ (λ x → ◇₂ (λ y → P x × Q y) ys) xs → ◇₁ P xs × ◇₂ Q ys
to (any (p₁ , any (p₂ , p , q))) = (any (p₁ , p) , any (p₂ , q))
from : ◇₁ P xs × ◇₂ Q ys → ◇₁ (λ x → ◇₂ (λ y → P x × Q y) ys) xs
from (any (p₁ , p) , any (p₂ , q)) = any (p₁ , any (p₂ , p , q))
-- map can be absorbed by the predicate.
module _ {s p} (C : Container s p) {x y} {X : Set x} {Y : Set y}
{ℓ} (P : Pred Y ℓ) where
map↔∘ : ∀ {xs : ⟦ C ⟧ X} (f : X → Y) → ◇ C P (map f xs) ↔ ◇ C (P ∘′ f) xs
map↔∘ {xs} f =
◇ C P (map f xs) ↔⟨ ↔Σ C ⟩
∃ (P ∘′ proj₂ (map f xs)) ↔⟨⟩
∃ (P ∘′ f ∘′ proj₂ xs) ↔⟨ SK-sym (↔Σ C) ⟩
◇ C (P ∘′ f) xs ∎
-- Membership in a mapped container can be expressed without reference
-- to map.
module _ {s p} (C : Container s p) {x y} {X : Set x} {Y : Set y}
{ℓ} (P : Pred Y ℓ) where
∈map↔∈×≡ : ∀ {f : X → Y} {xs : ⟦ C ⟧ X} {y} →
y ∈ map f xs ↔ (∃ λ x → x ∈ xs × y ≡ f x)
∈map↔∈×≡ {f = f} {xs} {y} =
y ∈ map f xs ↔⟨ map↔∘ C (y ≡_) f ⟩
◇ C (λ x → y ≡ f x) xs ↔⟨ ↔∈ C ⟩
∃ (λ x → x ∈ xs × y ≡ f x) ∎
-- map is a congruence for bag and set equality and related preorders.
module _ {s p} (C : Container s p) {x y} {X : Set x} {Y : Set y}
{ℓ} (P : Pred Y ℓ) where
map-cong : ∀ {k} {f₁ f₂ : X → Y} {xs₁ xs₂ : ⟦ C ⟧ X} →
f₁ ≗ f₂ → xs₁ ∼[ k ] xs₂ →
map f₁ xs₁ ∼[ k ] map f₂ xs₂
map-cong {f₁ = f₁} {f₂} {xs₁} {xs₂} f₁≗f₂ xs₁≈xs₂ {x} =
x ∈ map f₁ xs₁ ↔⟨ map↔∘ C (_≡_ x) f₁ ⟩
◇ C (λ y → x ≡ f₁ y) xs₁ ∼⟨ cong (Related.↔⇒ ∘ helper) xs₁≈xs₂ ⟩
◇ C (λ y → x ≡ f₂ y) xs₂ ↔⟨ SK-sym (map↔∘ C (_≡_ x) f₂) ⟩
x ∈ map f₂ xs₂ ∎
where
helper : ∀ y → (x ≡ f₁ y) ↔ (x ≡ f₂ y)
helper y rewrite f₁≗f₂ y = Inv.id
-- Uses of linear morphisms can be removed.
module _ {s₁ s₂ p₁ p₂} {C₁ : Container s₁ p₁} {C₂ : Container s₂ p₂}
{x} {X : Set x} {ℓ} (P : Pred X ℓ) where
remove-linear : ∀ {xs : ⟦ C₁ ⟧ X} (m : C₁ ⊸ C₂) → ◇ C₂ P (⟪ m ⟫⊸ xs) ↔ ◇ C₁ P xs
remove-linear {xs} m = Inv.inverse t f f∘t t∘f
where
open _≃_
open P.≡-Reasoning renaming (_∎ to _∎′)
position⊸m : ∀ {s} → Position C₂ (shape⊸ m s) ≃ Position C₁ s
position⊸m = ↔→≃ (position⊸ m)
◇₁ = ◇ C₁; ◇₂ = ◇ C₂
t : ◇₂ P (⟪ m ⟫⊸ xs) → ◇₁ P xs
t = Any.map₁ (_⊸_.morphism m)
f : ◇₁ P xs → ◇₂ P (⟪ m ⟫⊸ xs)
f (any (x , p)) =
any $ from position⊸m x
, P.subst (P ∘′ proj₂ xs) (P.sym (right-inverse-of position⊸m _)) p
f∘t : f ∘ t ≗ id
f∘t (any (p₂ , p)) = P.cong any $ Σ-≡,≡→≡
( left-inverse-of position⊸m p₂
, (P.subst (P ∘ proj₂ xs ∘ to position⊸m)
(left-inverse-of position⊸m p₂)
(P.subst (P ∘ proj₂ xs)
(P.sym (right-inverse-of position⊸m
(to position⊸m p₂)))
p) ≡⟨ P.subst-∘ (left-inverse-of position⊸m _) ⟩
P.subst (P ∘ proj₂ xs)
(P.cong (to position⊸m)
(left-inverse-of position⊸m p₂))
(P.subst (P ∘ proj₂ xs)
(P.sym (right-inverse-of position⊸m
(to position⊸m p₂)))
p) ≡⟨ P.cong (λ eq → P.subst (P ∘ proj₂ xs) eq
(P.subst (P ∘ proj₂ xs)
(P.sym (right-inverse-of position⊸m _)) _))
(_≃_.left-right position⊸m _) ⟩
P.subst (P ∘ proj₂ xs)
(right-inverse-of position⊸m
(to position⊸m p₂))
(P.subst (P ∘ proj₂ xs)
(P.sym (right-inverse-of position⊸m
(to position⊸m p₂)))
p) ≡⟨ P.subst-subst (P.sym (right-inverse-of position⊸m _)) ⟩
P.subst (P ∘ proj₂ xs)
(P.trans
(P.sym (right-inverse-of position⊸m
(to position⊸m p₂)))
(right-inverse-of position⊸m
(to position⊸m p₂)))
p ≡⟨ P.cong (λ eq → P.subst (P ∘ proj₂ xs) eq p)
(P.trans-symˡ (right-inverse-of position⊸m _)) ⟩
P.subst (P ∘ proj₂ xs) P.refl p ≡⟨⟩
p ∎′)
)
t∘f : t ∘ f ≗ id
t∘f (any (p₁ , p)) = P.cong any $ Σ-≡,≡→≡
( right-inverse-of position⊸m p₁
, (P.subst (P ∘ proj₂ xs)
(right-inverse-of position⊸m p₁)
(P.subst (P ∘ proj₂ xs)
(P.sym (right-inverse-of position⊸m p₁))
p) ≡⟨ P.subst-subst (P.sym (right-inverse-of position⊸m _)) ⟩
P.subst (P ∘ proj₂ xs)
(P.trans
(P.sym (right-inverse-of position⊸m p₁))
(right-inverse-of position⊸m p₁))
p ≡⟨ P.cong (λ eq → P.subst (P ∘ proj₂ xs) eq p)
(P.trans-symˡ (right-inverse-of position⊸m _)) ⟩
P.subst (P ∘ proj₂ xs) P.refl p ≡⟨⟩
p ∎′)
)
-- Linear endomorphisms are identity functions if bag equality is used.
module _ {s p} {C : Container s p} {x} {X : Set x} where
linear-identity : ∀ {xs : ⟦ C ⟧ X} (m : C ⊸ C) → ⟪ m ⟫⊸ xs ∼[ bag ] xs
linear-identity {xs} m {x} =
x ∈ ⟪ m ⟫⊸ xs ↔⟨ remove-linear (_≡_ x) m ⟩
x ∈ xs ∎
-- If join can be expressed using a linear morphism (in a certain
-- way), then it can be absorbed by the predicate.
module _ {s₁ s₂ s₃ p₁ p₂ p₃}
{C₁ : Container s₁ p₁} {C₂ : Container s₂ p₂} {C₃ : Container s₃ p₃}
{x} {X : Set x} {ℓ} (P : Pred X ℓ) where
join↔◇ : (join′ : (C₁ C.∘ C₂) ⊸ C₃) (xss : ⟦ C₁ ⟧ (⟦ C₂ ⟧ X)) →
let join : ∀ {X} → ⟦ C₁ ⟧ (⟦ C₂ ⟧ X) → ⟦ C₃ ⟧ X
join = λ {_} → ⟪ join′ ⟫⊸ ∘
_⟨$⟩_ (Inverse.from (Composition.correct C₁ C₂)) in
◇ C₃ P (join xss) ↔ ◇ C₁ (◇ C₂ P) xss
join↔◇ join xss =
◇ C₃ P (⟪ join ⟫⊸ xss′) ↔⟨ remove-linear P join ⟩
◇ (C₁ C.∘ C₂) P xss′ ↔⟨ SK-sym $ flatten P xss ⟩
◇ C₁ (◇ C₂ P) xss ∎
where xss′ = Inverse.from (Composition.correct C₁ C₂) ⟨$⟩ xss